Frontispiece: Can Bismuth Replace Mercury in Redox Transmetallation/Protolysis Syntheses from Free Lanthanoid Metals?. Issue 66 (28th November 2018) - Guo, Zhifang; Blair, Victoria; Deacon, Glen B.; Junk, Peter C.
Abstract : Synthesis of rare earth complexes from free rare earth metals offers advantages such as only one air/moisture sensitive reagent, and often simpler work up than metathesis reactions where alkali metal halide retention can be a problem. Redox transmetallation/protolysis reactions are highly successful but are inhibited by the use of toxic mercurials. Triarylbismuth compounds offer a possible greener alternative. For more information, see the Full Paper by P. C. Junk et al. onpage 17464 ff.